In Situ and in Vitro Nutritive Value Assessment of Styrax Officinalis L. as an Alternative Forage Source for Goat Feeding - Selim Esen; Evren Cabi; Levent Özdüven; Harun Karadağ; Hüseyin Eseceli; Fisun Koc (Journal of Agricultural Sciences)
The current study aimed to determine Styrax officinalis L. (SO) leaf's nutritive value, collected at four phenological stages, pre-flowering (PF), flowering (FL), seed linkage (SL), and fruiting (FR) by in situ and in vitro experiments. The ruminal degradability of dry matter (DM) and crude protein (CP) and in vitro gas production (GP) of SO leaves were measured using three rumen fistulated mature Saanen goats. Significant differences between chemical compositions of the SO leaves collected at different phenological stages were observed (P<0.001). The DM, CP, ether extract (EE), and ash values of SO leaves ranged between 29.16 to 45.63%, 10.11 to 19.79%, 3.40 to 5.85%, and 4.71 to 6.49% during the different phenological stages (PF, FL, SL and FR, respectively). Cell wall components of SO leaves showed a cubic trend due to their capability to form new shoots after grazing. The effective DM and CP degradability of SO leaves ranged between 66.91 to 77.93% and 64.92 to 84.57%, which means an average value for animals fed at approximately maintenance level when rumen outflow rate (r) is equal to 0.02 h−1. Significant differences between the SO leaves collected at different phenological stages were observed in GP at all incubation times (P<0.05 and P<0.001). After 96 h incubation, the gas produced ranged between 20.68 to 27.53 mL/200 mg DM of the substrate. The research findings clearly indicate that degradability of DM, CP, and ME content of SO leaves ranged between moderate to high and significantly affected by phenological stages, however, they could be utilized until the end of the FL stage as forage sources.